Integrated evaluation of targeted and non‐targeted therapies in a network meta‐analysis - Proctor, Tanja; Jensen, Katrin; Kieser, Meinhard (Biometrical journal, 2020)
Individualized therapies for patients with biomarkers are moving more and more into the focus of research interest when developing new treatments. Hereby, the term individualized (or targeted) therapy denotes a treatment specifically developed for biomarker‐positive patients.
First published: 23 September 2019
Correction added on 28 October 2020, after first online publication: Projekt Deal funding statement has been added
Gesehen am 26.01.2021